Karakalpak Zhyrau Art: Current Situation, Important Issues of Future - G.M. Egamkulova (Zien Journals, 2022)
The article tells about the ancient art tradition of the Karakalpaks - zhyrau. There are material remnants of ancient civilizations in the world today. However, Karakalpak Zhyrau art is a well-preserved cultural heritage. The author fears that if the government does not develop the art of singing, it will not reach the next generation. The author also comments on establishing close relations with the Nurata Zhyrau school.
Keywords: Zhyrau; Bakhshi; Zhyrau school; Nurata